Lexical-semantic abilities and executive functions in the elderly - Vuković, Mile; Stanković, Ana (Specijalna edukacija i rehabilitacija, 2023)
Lexical-semantic abilities and executive functions in the elderly Introduction. The development of modern society has led to an increase in the life expectancy, and thus to a significant increase in the number of elderly people. Therefore, in recent years a lot of attention has been paid to the examination of cognitive abilities in this population. The research focuses on changes in language, executive functions and memory. Aim. This study aimed to determine lexical-semantic abilities and executive functions in persons over the age of 65. Methods. The sample included 30 people ranging in age from 66 to 85. The respondents were divided into two age categories, with 16 respondents from the "young old" category and 14 respondents in the "middle-old and oldest-old" category. The sample included 13 respondents who had finished elementary school and 17 respondents who had finished secondary or higher/university education. The Semantic Test and the Verbal Fluency Test were used to assess lexical-semantic abilities. To assess executive functions, the Stroop test was used. Results. The results have shown that respondents with different age categories do not differ in their achievements on tests for the assessment of lexical-semantic abilities. However, differences in achievements were determined in relation to the level of education of the respondents. People with a higher educational level were more successful on the mentioned tests. Furthermore, the results show a difference in achievement on the test for assessing executive functions based on age and level of education. Conclusion. These findings indicate that executive functions are more sensitive to age than lexical-semantic abilities.